KARMA MARGA DALAM BHAGAVADGITA SEBAGAI LANDASAN MEMBANGUN KESUCIAN KERJA - Aryani, Ni Luh (Widya Sandhi, 2018)
This study aims to conduct studies on building sanctity of work based on the teachings of karma marga in the Bhagawadgita holy book. Based on the results of the analysis found that in the teachings of karma marga there are sloka-sloka that emphasizes the values that can build morale in order to realize eternal freedom. Humans living in this world are forced by the laws of nature to act. The act is called the karma marga as part of yadnya, so that the work done is not based on self-interest and without self-interest. Work is a cycle in order to realize perfection in this life, because life needs food and food caused by rain, rain caused by yadnya and yadnya because of karma or action. Through the work of perfection can be realized. Work done should be based on swadharma, because it can purify themselves in order to achieve perfection. The doctrine becomes the basis in order to establish the sacredness of work.